Development of Problem-Based Learning E-Module in Junior High Schools 15 Yogyakarta - Derunansyah, Sheldy; Prasetyo, Puguh Wahyu; Khasanah, Uswatun (Universitas Ahmad Dahlan, 2024)
Algebra is a concept that is abundant in everyday life, connecting symbols with contextual problems. The challenge of learning algebraic forms is apparent among seventh-grade students at SMP N 15 Yogyakarta, who have a low mathematical literacy. The initial research findings show variability in the components of mathematical literacy among students, including Communication (23%), Mathematicalization (20%), formulation of Problem-Solving Strategies (11%), Reasoning and Argumentation (12%), Symbolic, Formal, and Technical Language Usage, and Operations (2%), Representation (18%), and use of Mathematical Tools (18%). One of the reasons for the low literacy is the learning model and the material is less suitable. This research aims to develop a PBL-based e-Module to improve students' mathematical literacy in algebraic forms. The research method used is R&D with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research instruments include expert validation of materials and media, student responses, and pretests. The developed e-Module received good validation from media experts (average 4.33) and material experts (average 4.63). Student responses were also positive, averaging 82% falling into the practical category. The conclusion is that this e-Module is suitable for use as a tool for improving students' mathematical literacy.